Recent Trends on Dual- and Triple-Band Microwave Filters for Wireless Communications - Zakaria, Z; Omar, N; Othman , A. R; Jawad, M. S; Ismail, A; Salleh, A; Sam , W. Y (2013)
In the past few years, several designs of dual- and triple-band microwave filters satisfying various objectives have been proposed for wireless communication. Several designs are new concepts, whereas others are inspired from previous works. The development trends of these designs can be reviewed from this compilation of studies. This paper begins with an explanation of dual- and triple-band microwave filters, followed by a discussion on several designs in terms of size, measurement, performance, and technology use. Among various designs, microstrip band-pass filters are extensively used because of their simple design procedures and because they can be integrated into circuits easily. Furthermore, most researchers use low frequencies in their designs because of the demands of current wireless applications. Finally, designs are proposed to produce compact microwave filters with good performance.